2013
DOI: 10.5395/rde.2013.38.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epigallocatechin Gallate on shear bond strength of composite resin to bleached enamel: anin vitrostudy

Abstract: ObjectivesThe aim of this study was to determine the effect of epigallocatechin gallate (EGCG) on the shear bond strength of composite resin to bleached enamel.Materials and MethodsNinety enamel surfaces of maxillary incisors were randomly divided into 9 groups as follows: G1: control (no bleaching); G2: bleaching; G3: bleaching and storage for seven days; G4 - 6: bleaching and application of 600, 800 and 1,000 µmol of EGCG-containing solution for 10 minutes, respectively; G7 - 9: bleaching and application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
1
22
0
11
Order By: Relevance
“…Thus, there is need to study alternative antioxidants that are able to completely reverse the reduction in bond strength of bleached enamel. For this reason, the present study evaluated GT as an alternative to SA and the results showed to be satisfactory, as reported when EGCG, the most active and abundant catechin in GT, was tested (14). EGCG applied for 10 min was able to overcome the compromised bonding strength.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, there is need to study alternative antioxidants that are able to completely reverse the reduction in bond strength of bleached enamel. For this reason, the present study evaluated GT as an alternative to SA and the results showed to be satisfactory, as reported when EGCG, the most active and abundant catechin in GT, was tested (14). EGCG applied for 10 min was able to overcome the compromised bonding strength.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, a potent antioxidant is needed able to reverse the bond strength values and clinically viable. Additionally, recent studies have shown that the green tea is an antioxidant alternative for use after bleaching (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Khamaverdi et al [26] tested the application for 10 min of EGCG, the most active and abundant catechin present in green tea, and found that this time was sufficient to increase the shear bond strength values of the enamel to the composite resin. In the present study, we used the green tea with 60 % catechins without standardization of the EGCG content.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research concerns raise the attention on the effects of natural herbal extracts. Numerous studies have indicated the anticancer, antibacterial and antioxidant effects of different plant extracts [27][28][29]. In addition, herbal products are non-cytotoxic, easily accessible, with a long shelf life [30].…”
Section: Blockmentioning
confidence: 99%